1998
DOI: 10.1086/516316
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of and Immunologic Alterations Caused by Interferon g Therapy for Alveolar Echinococcosis

Abstract: Alveolar echinococcosis (AE) is a rare and often fatal disease characterized by a tumorlike expansion of the metacestode Echinococcus multilocularis in the liver. Because of the severe side effects of therapy with benzimidazoles, we treated a patient with recombinant interferon gamma at a dose of 250 microg over a 3-day period once a month. Disease progression was not detected during the observed period of 18 months. Following stimulation with crude Echinococcus antigen, mRNA from interleukin 5 was still detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 12 publications
3
23
0
2
Order By: Relevance
“…Two case reports documented the clinical efficacy of IFN-c-treatment. One patient suffering from severe side-effects caused by ABZ-therapy was treated with IFN-c during a 3-day period once a month, and this treatment prevented disease progression but did not alter the Th2-dominated immune response against this parasite (Jenne et al 1998). Another patient whose lesions were growing, despite mebendazole therapy, was treated with a combination of IFN-c and mebendazole, which halted the progression of disease as revealed in a 1-year follow-up period (Schmid et al 1995).…”
Section: Alveolar Echinococcosis (Ae)mentioning
confidence: 99%
“…Two case reports documented the clinical efficacy of IFN-c-treatment. One patient suffering from severe side-effects caused by ABZ-therapy was treated with IFN-c during a 3-day period once a month, and this treatment prevented disease progression but did not alter the Th2-dominated immune response against this parasite (Jenne et al 1998). Another patient whose lesions were growing, despite mebendazole therapy, was treated with a combination of IFN-c and mebendazole, which halted the progression of disease as revealed in a 1-year follow-up period (Schmid et al 1995).…”
Section: Alveolar Echinococcosis (Ae)mentioning
confidence: 99%
“…It also inhibited IL-6 and IL-13 antigen-induced secretions in spleen cell cultures. Jenne et al (1998) reported a case of a 61 year old patient with Echinococus multilocularis infection of the lungs, liver, pericardium, bones and brain, which relapsed after 19 years of antiparasitic chemotherapy. This patient received 16 cycles of recombinant IFN-gamma; in total 250 µg monthly for 16 months.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-gamma is the component part of the Th1 answer (together with interleukin-2 induced by interleukin-12), in the dominance of the Th1 response over the Th2 response reduction of echinococcal loci in the liver was noticed ( Vuitton & Gottstein, 2010). The IFN treatment prevents the echinococcal lesions growth in animal as well as human model (Liance et al, 1998;Jenne et al, 1998). Anti-parasitic treatment leads to IFN-gamma level increase ( Dvorožňáková et al, 2004).…”
Section: A 1bmentioning
confidence: 99%